Lactoperoxidase enzyme activity and thiocyanate levels in raw milk of Girolando cows - Freitas, Wandemberg Rocha; Nascimento, Talita Camila Evaristo da Silva; Lins, Leandro Fragoso; Silva, Janaina de Lima; Moreira, Keila Aparecida; Batista, Ângela Maria Vieira; Barbosa, Severino Benone Paes (Medicina Veterinária, 2020)
Considering the importance of milk enzymes in milk preservation and animal protection, this study aimed to identify the factors that influence lactoperoxidase activity and levels of thiocyanate in raw milk of Girolando cows, as well as to verify the correlation between these components and the number of somatic cells in cooled raw milk. A total of 181 of milk samples from Girolando cows were used to determine the lactoperoxidase activity, thiocyanate levels, somatic cell number, and serum protein content. The genetic group and the sampling period influenced lactoperoxidase activity. Thiocyanate levels were influenced by the sampling period and by the interaction between the genetic group and the sampling period. The number of somatic cells was influenced by the number of days in lactation, animal age, and sampling period. Milk of animals from the group 1/2 Holstein x Gyr had the highest lactoperoxidase activity and there was no influence of the genetic group on the levels of thiocyanate.